Agricultural carbon productivity in China: calculation and spatio-temporal differences - Wang Xinyao; Li Dan (Cogent Food & Agriculture)
To achieve the ‘dual carbon’ goal, it is imperative for China to pursue a pathway towards low-carbon agricultural development, with a primary focus on enhancing agricultural carbon productivity comprehensively. This paper calculates agricultural carbon emissions from the perspectives of rice field methane, nitrous oxide from agricultural land, methane from animal enteric fermentation, methane and nitrous oxide from animal manure management, agricultural energy, crop straw burning, and land use change and forestry carbon sinks. Based on this, this paper measures the agricultural carbon productivity across 31 provinces (autonomous regions and municipalities) in China from 2000 to 2020 and examines its spatial and temporal evolution and convergence. The findings reveal that: Firstly, China’s green and low-carbon agricultural development is relatively slow. Secondly, there is a clear gap in agricultural carbon productivity between provinces in China. The average contribution of agricultural carbon productivity differences between provinces to regional differences is 70.57%. Thirdly, only there is absolute β convergence in the eastern region, but China’s agricultural carbon productivity has a notable conditional β convergence trend. The eastern regions tend to exhibit a high-high agglomeration characteristics. Therefore, it is necessary to formulate regionally differentiated agricultural carbon productivity growth strategies and foster the harmonized advancement of environmentally friendly and low-carbon agriculture across all provinces.